Modified Chaotic Key-Based Algorithm for Image Encryption and its VLSI Realization - Deergha Rao, K.; Gangadhar, Ch (2007 15th International Conference on Digital Signal Processing, 2007)
Chaos based encryption may offer new quality in secure data transmission. A recently proposed chaotic-key based algorithm (CKBA) has been shown to be unavoidably susceptible to chosen/known-plaintext attacks and ciphertext-only attacks. In this paper, modified chaotic-key based algorithm (MCKBA) is proposed to enhance the security of CKBA. The enhanced security of the proposed algorithm is analyzed through cryptanalysis. Further, VLSI architecture of the proposed algorithm is designed. The VLSI architecture is implemented on an image using XILINX's ModelSim to demonstrate the effectiveness of the proposed scheme.